EX OFFICIO JUDGE'S AUTHORITY TOWARDS FULFILLMENT OF WOMEN'S AND CHILDREN'S RIGHTS AFTER DIVORCE AS REVIEWED FROM THE PRINCIPLE OF ULTRA PETITA - Helpan Setiabudi; Abdul Rachmad Budiono; Hanif Nur Widhiyanti (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the ex officio authority of judges and the ultra petita principle in divorce cases in Religious Courts, as well as their implications for the protection of women's and children's rights. The background of this study is based on the fact that divorce cases in Indonesia continue to increase annually, but only a small proportion of decisions contain the determination of women's and children's rights after divorce without a request from the litigants. This study uses a normative legal research method with a statutory, case, and conceptual approach. Data sources consist of primary, secondary, and tertiary legal materials, analyzed using description, interpretation, evaluation, and systematization techniques. The results show that ex officio authority is an important instrument held by judges to protect the rights of vulnerable parties in divorce cases, such as determining iddah (waiting period), mut'ah (waiting for temporary dowry), child custody, and child living expenses. However, its application often clashes with the ultra petita principle, which limits judges from deciding cases beyond what the parties request. The tension between these two principles leads to inconsistent decisions, which impacts on the suboptimal protection of women's and children's rights. This study concludes that there is a need to harmonize ex officio authority and the ultra petita principle through clear technical guidelines and training for judges, so that substantive justice and legal certainty can be achieved in a balanced manner. Recommendations include strengthening judges' understanding of the protection of vulnerable groups, utilizing socio-economic data in decisions, and consistent application of ex officio authority across all Religious Courts.